2012
DOI: 10.1161/circulationaha.111.076257
|View full text |Cite
|
Sign up to set email alerts
|

Survival After Alcohol Septal Ablation for Obstructive Hypertrophic Cardiomyopathy

Abstract: Background-The clinical efficacy of alcohol septal ablation for obstructive hypertrophic cardiomyopathy (HCM) has been demonstrated, but the long-term effects of the procedure remain uncertain. This study examined the survival of patients after septal ablation performed in a tertiary HCM referral center. Methods and Results-We examined 177 patients (mean age, 64 years; 68% women) who underwent septal ablation at our institution. Over a follow-up of 5.7 years, survival free of all mortality was no different tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
170
4
13

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(209 citation statements)
references
References 34 publications
(57 reference statements)
19
170
4
13
Order By: Relevance
“…And, as survival after myectomy, survival after ASA is also comparable with that of general population [8,9]. These data support the notion that ASA may be another intervention which improves survival of patients with obstructive HCM and severe drug-refractory symptoms.…”
Section: Introductionsupporting
confidence: 74%
See 2 more Smart Citations
“…And, as survival after myectomy, survival after ASA is also comparable with that of general population [8,9]. These data support the notion that ASA may be another intervention which improves survival of patients with obstructive HCM and severe drug-refractory symptoms.…”
Section: Introductionsupporting
confidence: 74%
“…However, we are still not sure whether this technique extends longevity of its target patients. Results from several studies suggest that ASA can extend longevity of patients with HCM [6][7][8][9][10][11][12]. Here, we extended evidence for this notion by directly comparing the survival of patients undergoing ASA vs. a group of conservatively treated patients with comparable pressure gradient and limiting symptoms.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Additionally, he was also started with off-label sildenafil with an aim for the reduction of significant pulmonary hypertension. Based on the literature and an experience the clinical efficacy of alcohol septal ablation for HCM is good in terms of symptoms relief but it's long-term effect remains uncertain [6]. Our patient underwent alcohol ablation of basal segment of interventricular septum due to symptoms resulting from LVOT obstruction.…”
Section: Discussionmentioning
confidence: 98%
“…Such fears were heightened by some small observational studies, 32,33 but these were contradicted by other similar studies that indicated the technique was safe. 34,35 These conflicting results, and the lack of sufficient evidence, have created confusion that can only be resolved by large studies of patients treated by ASA with long-term outcomes and by meta-analyses comparing the results of the two techniques. In 2008 Kuhn et al published the results of 644 consecutive patients treated by ASA over a 10-year period.…”
Section: Comparison With Myectomymentioning
confidence: 99%